Relationship of functional balance and cognitive impairment in elderly. - Santos, Mayra Campos Frâncica dos; Santos, João Paulo Manfré dos; Fontanela, Vanessa; Spricio, Solaine Melchior; Gil, André Wilson de Oliveira; Pires-Oliveira, Deise Aparecida de Almeida (Manual Therapy, Posturology & Rehabilitation Journal, 2014)
Introduction: Population aging brings physical changes of its own age. Along with these changes occur in most cases, the comorbidities that maximize the geriatric syndromes. Balance disorders are the class of the most important factors when it comes to instability and falls in the elderly. Thus, the knowledge of what generates or which is associated with balance deficits and therefore predispose the elderly to fall is critical to reduce the frequency of them, but also to the severity of its sequelae. Objective: To analyze the relationship between cognitive performance and functional balance in elderly institutionalized and community. Method: The sample consisted of 36 participants and 19 older adults and 17 elderly subjects, recruited voluntarily and for convenience. The evaluation presented by sociodemographic form, analyze the risk of falls (TUG) and the Mini Mental State Examination (MMSE), which was used for screening of cognitive impairment in the elderly. Results: Through the anthropometric analysis, community elders had a mean age of 73.11 years, weighing 66.90 kg and height of 1.56 m, as the institutionalized group had an average age of 72.06 years, average height and weight 69.88 kg 1.60 m. Elderly community, physically active, showed lower risk for falls compared to elderly subjects (p<0.001), in addition to having better cognitive performance (p=0.002). A moderate correlation between the TUG and the MMSE (r=–0.513) was also found. Conclusion: Both groups were made up of active seniors, both community and institutionalized, however community elders showed better cognitive status and a lower risk of falls in relation to the institutionalized elderly, noting that the cognitive status increases the risk of falls.